INTERNALIZATION OF SOCIAL CARE VALUES WITH INFAQ: CASE STUDY AT MTSN 6 PONOROGO, EAST JAVA, INDONESIA - Daroini, Islam; Ikhwan, Afiful; Saputro, Anip Dwi (Universitas Islam Negeri Raden Intan Lampung, 2020)
This research is aimed to invest the students’ social care since the begining to establish the character of the students to attain the prosperous and happy life by implementing infaq in the social life. This study implemented qualitative method. The data was gained by interviewing from the stakeholder of institution, observation and documentation technique that analyzing by Miles and Huberman data reduction, data display and verification. Besides, it was also using triangulation; credibility, transferring, dependability and confirm-ability to check the data valdity. This study was conducted at MTsN 6 Ponorogo East Java. This study revealed that infaq plays important role that influence one of human character in Islamic perspectives. It has an obligation to embed social sense as a community which has interaction in social community. The social gaps will never happen if they were knowing and helping each other. Thus, Infaq become solution that it will empower the social life in community that occur good harmony relationship between school’s stakeholder, teacher, students and social community.